2013
DOI: 10.34194/geusb.v28.4722
|View full text |Cite
|
Sign up to set email alerts
|

The norite belt in the Mesoarchaean Maniitsoq structure, southern West Greenland: conduit-type Ni-Cu mineralisation in impact-triggered, mantle-derived intrusions?

Abstract: With the recent discovery of the giant, deeply eroded, 3 Ga Maniitsoq impact structure in southern West Greenland (Garde 2010), an enigmatic, c. 75 by 15 km large, curvilinear belt of undeformed norite intrusions with Ni-Cu mineralisation was re-interpreted as representing crustally contaminated melts derived from the mantle in the wake of the impact (Fig. 1; Garde et al. 2012). The norite belt (Nielsen 1976; Secher 1983) was discovered in the early 1960s by the mining and exploration company Kryolitselskabet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…These intrusions were reinterpreted by Garde et al. (, ) as representing mantle melts with continental crustal contamination, triggered by the proposed impact. One of them yielded three poorly defined 207 Pb/ 206 Pb age groups at 3016 ± 23 Ma, 3006 ± 13 Ma, and 2976 ± 13 Ma (Garde et al.…”
Section: Correlation With Previously Published Age Data From the Soutmentioning
confidence: 91%
See 2 more Smart Citations
“…These intrusions were reinterpreted by Garde et al. (, ) as representing mantle melts with continental crustal contamination, triggered by the proposed impact. One of them yielded three poorly defined 207 Pb/ 206 Pb age groups at 3016 ± 23 Ma, 3006 ± 13 Ma, and 2976 ± 13 Ma (Garde et al.…”
Section: Correlation With Previously Published Age Data From the Soutmentioning
confidence: 91%
“…These include a regional aeromagnetic anomaly; a thoroughly comminuted core (Finnefjeld domain) measuring 35 by 50 km; extensive in situ lower crustal crush zones with segregation of K‐feldspar melt veins; a surrounding, approximately 20 km wide melt zone with direct melting of feldspar; the above‐mentioned belt of noritic intrusions, which are interpreted as representing crustally contaminated mantle melts (Garde ; Garde et al. ); and superimposed, very intense, high‐temperature hydrothermal alteration in large parts of the structure.…”
Section: Previously Published Evidence For Impact At Maniitsoqmentioning
confidence: 99%
See 1 more Smart Citation
“…Garde et al (2012) and (2013) suggested a genetic link to the "post-kinematic diorites" of the Fiskefjord region (Garde, 1991), which along with recently discovered norite outcrops to the north of the main norite belt (Ravenelle et al, 2017) imply norite magmatism occurred over length scales >100 km. Norite bodies range in size from kilometre-scale (e.g., the 8 km 2 Fossilik body; Ravenelle et al, 2017) to meter-scale pods (Garde et al, 2013). Unlike other mafic-ultramafic complexes further south in the Akia Terrane (Garde, 1997;Szilas et al, 2015), the norites are not closely associated with other ultramafic cumulates.…”
Section: The Maniitsoq Norite Beltmentioning
confidence: 99%
“…Despite significant interest in the ∼2.7-2.0 Ga noritic suite, there are few documented occurrences of "boninite-like" noritic rocks older than 2.7 Ga. In this regard, the exposed North Atlantic Craton in West Greenland may be unusual, with norites reported in the ∼3 Ga Maniitsoq Norite Belt and associated "diorite" of the Fiskefjord region (Garde, 1991;Garde et al, 2013;Ravenelle et al, 2017), the ∼3 Ga Amikoq Complex (Aarestrup et al in press), and ∼3.4 Ga noritic dykes in the Isua region (Nielsen et al, 2002). In this study, we present new field observations, petrography, geochemical and isotopic data, and phase equilibrium modelling for the ∼3 Ga Maniitsoq Norite Belt, with the aim of understanding its petrogenesis.…”
Section: Introductionmentioning
confidence: 99%